Technological innovations and their impact on higher economic skills and studies: realities and perspectives (International Journal of Scientific Research and Management (IJSRM), 2023)
Lately, innovation has become an inevitable notion in all fields of activity, innovation based on technology, on products, on processes, innovation in the behavioural approach. The beneficial effects of innovation are undeniable, but few studies have investigated this phenomenon, particularly in terms of the skills it requires, the labour market, how it will affect economic specialities and the number of specialists in this field. The aim of this article is to study the effect of innovation on the training of economic specialists and the skills required. How the structure of specialisations will change, the number of specialists needed on the labour market will change, as a result of digitisation and IT-based business models. Research methods: comparative analysis of the skills required by employers compared to those currently provided, deduction of future needs in relation to future professions, modelling of the scenario of existence of future universities. As a result of the research we propose to identify the future specialties with an economic profile as a result of the application of information technologies with an economic profile, the required competences, the most effective study/learning methods, the determination of the university/economic studies in the futu re.